Potential Increasing Trend in Schizophrenia Relapse Prevention in the Past 40 Years: A Bibliometric Analysis - Isymiarni Syarif; Hasnawati Amqam; Saidah Syamsuddin; Veni Hadju; Syamsiar Russeng; Yusran Amir (Korean Society for Preventive Medicine, 2024)
Objectives: Schizophrenia is an organic disease and a severe mental disorder with a relatively high risk of relapse. The rising rate of schizophrenia relapse has motivated researchers and academics to innovate and develop interventions aimed at relapse prevention. This bibliometric study sought to examine the publication trends in schizophrenia relapse prevention from 1973 to 2023, assess the contribution of international collaborations across various journals, identify the most influential authors and articles, and forecast future developments in this field. Methods: The study included 683 articles obtained from the Scopus database, analyzed using VOSviewer software, and visualized with Tableau. Results: Reports of schizophrenia relapse prevention strategies have increased significantly over the last 3 decades. However, fluctuations persist, as evidenced by the annual number of publications ranging from 25 to 40 within the past 5 years. Nevertheless, this increasing trend underscores the sustained interest in this area of research. Regarding contribution size, the United States produced the largest volume of publications on this subject. John M. Kane authored the most articles, while Stefan Leucht exhibited the highest h-index. Frequently used keywords in this field include "relapse AND schizophrenia" AND "prevention." Conclusions: These results represent an important reference for determining the current state of research on schizophrenia relapse prevention and future research directions.